Safari juice / Muhammad Faiz Hazim Hasbullah - Hasbullah, Muhammad Faiz Hazim (Universiti Teknologi MARA, Kedah, 2025)
For this final project, I studied a product aimed at proposing a redesign of Norza Dlekir, which is famous in Seri Manjung, Perak. Muhammad lkmal is the founder of this Norza Dlekir product in 2017. With the wide demand for bumiputera juice, he has made him to produce halal and quality juice. With this, I am happy to introduce the new name of Safari Juice which is more attractive, easy to remember, and suitable for all walks of life to know. The name is inspired by the beauty and wonder of Malaysia's rainforest, known for their wealth of natural resources, including a variety of unique and mesmerizing tropical fruits. Our rainforest is not only a symbol of our amazing biodiversity but also the inspiration for the taste and freshness we combine in every bottle of Safari Juice. With the spirit of appreciating nature, Safari Juice is more than just a drink, it is a taste experience that brings you closer to the beauty and bounty of the Malaysian rainforest. This fruit juice highlights a unique character with each animal symbolizing the fruit that is often their choice. For example, monkeys who like to enjoy bananas. rich in natural nutrients; elephants who love sweet and refreshing melons; as well as wildebeests enjoying mangosteen. the queen of tropical fruits. These animals are not only icons of the wild life of the Malaysian rainforest but also symbols of species that are now on the verge of extinction. Safari Juice is not just a drink, it is a reminder of the beauty and importance of protecting these animals and keeping the tropical rainforest rich with freshness and tranquility of nature. Through Safari Juice. we are invited to appreciate Malaysia's nature. Safari Juice offers fresh. natural fruit juices that delight the palate while celebrating the beauty of Malaysia's tropical rainforest. Through effective strategies such as billboards. creative campaigns and active engagement on lnstagram. we share the unique story of the rainforest and inspire appreciation for nature. Every sip of Safari Juice connects you with the authenticity of fresh fruit and the beauty of the rainforest. reminding us of its rich biodiversity and the importance of preserving it. With Safari Juice. the beauty of nature becomes part of your everyday life.